Dans les pas d’un ministre, dans les rouages d’un ministère - Sylvain Laurens (Temporalités)
Studying the personal agendas of a cabinet director working in a Ministry in the 1970s shows the work such a position entailed on a daily basis. The agendas are first analysed statistically and qualitatively in order to understand how, in such a pivotal role, a director must arbitrate between the different temporalities involved in tasks relating to administration, politics and communication. In France, a Minister’s chief of staff occupies a unique place in the division of labor. Transmitting information to several social scenes, he is the focal point on which the tensions generated by administrative and political work refract. Counting the number of meetings and the persons encountered, we will see what proportion of working time is actually devoted to each of these tasks. What time does the chief of staff spend in the footsteps of his minister or inside the ministry (where he “mans” the office)? It is also possible to gauge whether the distribution of time between those various expectations is stable or not during a minister’s term and when nearing election time.